Bloodless ebook - Preston, Douglas (Pendergast, 2021)
INSTANT #1  NEW YORK TIMES  BESTSELLER: Agent Pendergast faces his most unexpected challenge yet when bloodless bodies begin to appear in Savannah, GA. A fabulous heist: On the evening of November 24, 1971, D. B. Cooper hijacked Flight 305—Portland to Seattle—with a fake bomb, collected a ransom of $200,000, and then parachuted from the rear of the plane, disappearing into the night…and into history. A brutal crime steeped in legend and malevolence: Fifty years later, Agent Pendergast takes on a bizarre and gruesome case: in the ghost-haunted city of Savannah, Georgia, bodies are found with no blood left in their veins—sowing panic and reviving whispered tales of the infamous Savannah Vampire. A case like no other: As the mystery rises along with the body count, Pendergast and his partner, Agent Coldmoon, race to understand how—or if—these murders are connected to the only unsolved skyjacking in American history. Together, they uncover not just the answer…but an unearthly evil beyond all imagining.